Motor Cortex and Hippocampus Display Decreased Heme Oxygenase Activity 2 Weeks After Ventricular Fibrillation Cardiac Arrest in Rats - Warenits, Alexandra-Maria; Hatami, Jasmin; Müllebner, Andrea; Ettl, Florian; Teubenbacher, Ursula; Magnet, Ingrid Anna Maria; Bauder, Barbara; Janata, Andreas; Miller, Ingrid; Moldzio, Rudolf; Kramer, Anne-Margarethe; Sterz, Fritz; et al. (Frontiers in Medicine, 2020)
Heme oxygenase (HO) and biliverdin reductase (BVR) activities are important for neuronal function and redox homeostasis. Resuscitation from cardiac arrest (CA) frequently results in neuronal injury and delayed neurodegeneration that typically affect vulnerable brain regions, primarily hippocampus (Hc), motor cortex (mC), but occasionally also striatum and cerebellum. We questioned whether these delayed effects are associated with changes of the HO/BVR system. We therefore analyzed the activities of HO and BVR in the brain regions Hc, mC, striatum and cerebellum of rats subjected to ventricular fibrillation CA (6 min or 8 min) after two weeks following resuscitation, or sham operation. From all investigated regions, only Hc and mC showed significantly decreased HO activities, while BVR activity was not affected. In order to find an explanation for the changed HO activity, we analyzed protein abundance and mRNA expression levels of HO-1, the inducible, and HO-2, the constitutively expressed isoform, in the affected regions. In both regions we found the tendency for a decreased immunoreactivity of HO-2 using immunoblots and immunohistochemistry. Additionally, we investigated the histological appearance and the expression of markers indicative for activation of microglia (tumor necrosis factor receptor type I (TNFR1) mRNA and immunoreactivity for ionized calcium-binding adapter molecule 1 (Iba1)), and activation of astrocytes (immunoreactivity for glial fibrillary acidic protein (GFAP)) in Hc and mC. Morphological changes were detected only in Hc displaying loss of neurons in the cornu ammonis 1 (CA1) region, which was most pronounced in the 8 min CA group. In this region also markers indicating inflammation and activation of pro-death pathways (expression of HO-1 and TNFR1 mRNA, as well as increased Iba1 and GFAP immunoreactivity) were upregulated. Since HO products are relevant for maintaining neuronal function, our data suggest that neurodegenerative processes following CA may be associated with a decreased capacity to convert heme into HO products in particularly vulnerable brain regions.